Recent Security Features of 5G Protocol for Real Time Network Domain – An Overview - Smys, S. (Journal of ISMAC, 2022)
Numerous mission-critical applications in the field of information technology will rely on fifth generation (5G) networks in the future. The 5G is projected to bring new technological improvements and innovation. Software-Defined Networking (SDN) is the present backbone of 5G. Because of the specific needs of each application that may be met by network slicing, 5G can provide this feature. In comparison to 4G Long-Term Evolution (LTE) and preceded generations, 5G is more adaptable and scalable. However, considerable advances in 5G cyber security are required to minimise the rising threats of hacking. Both the network and the devices linked to 5G are subjected to security problems. 5G communication networks' weaknesses may create many dangerous unknown attacks. However, it depends on the 5G privacy and security key protocol. In addition, several dangerous attacks may be combined to provide a wide range of attack options for hackers. For the 5G communication network, this article provides a complete framework for security analysis. The findings of this study might lead to unique 5G communication exploits. Moreover, artificial intelligence learning has been recently used to create and analyse attack graphs for software-defined and virtualized 5G communication networks.
Keywords: 5G edge securities; vulnerability analysis; 5G security; mobile network security; IoT; smart agriculture; agriculture robots